2010
DOI: 10.1517/14728214.2010.512610
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs for diabetic neuropathy

Abstract: DN is a very common and disabling complication that currently has no effective treatments other than diabetes control. The pathogenesis of DPN is complex and multi-factorial. Several disease-modifying and symptomatic treatments are currently under development. Oxidative and nitrosative stress have been identified as key pathogenic factors in the development of DPN and new treatments target these pathways and/or their downstream consequences. Gene therapy and growth factors have also emerged as potential new th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 176 publications
1
33
0
11
Order By: Relevance
“…Advanced glycation end products (AGEs) and oxidized lipoproteins activate inflammatory signaling, which leads to oxidative and nitrosative stress, which in turn aggravates the inflammation [4,33] . Therefore, clearance of oxidative and nitrosative stress and inhibition of inflammation have been considered good strategies for the treatment of diabetic neuropathy [34] . Prior studies have shown that quercetin has a good capacity for scavenging ROS and yielding neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) and oxidized lipoproteins activate inflammatory signaling, which leads to oxidative and nitrosative stress, which in turn aggravates the inflammation [4,33] . Therefore, clearance of oxidative and nitrosative stress and inhibition of inflammation have been considered good strategies for the treatment of diabetic neuropathy [34] . Prior studies have shown that quercetin has a good capacity for scavenging ROS and yielding neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Causal pathways to foot ulceration are multifactorial and involve combinations of physiological and mechanical factors, self-care, and treatment factors. Diabetic nephropathy has been identified to be an important risk factor for DFI and amputation [25,26]. Present highlighted that in patients with DFI there is a reduction in eGFR and when the infection subsides the eGFR improved, whereas in patients with pre-existing CKD the decrease in eGFR was observed in all the follow-up periods.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, there is a need to determine effective therapeutic strategies aimed at preventing microvascular complications associated with diabetes 1,4 . Such strategies should apparently be aimed at correcting the pathophysiological and biochemical alterations associated with diabetes 2,5 .…”
Section: Issn: 0975-8232mentioning
confidence: 99%
“…Thus, early commencement of anti-oxidant supplementation along with a powerful neuroprotective agent could effectively prolong, if not prevent the progression of DN 5 . With this hypothesis, we aimed to determine the effect of early coadministration VEM on DN in laboratory rats.…”
Section: Issn: 0975-8232mentioning
confidence: 99%